Back Cover: Polymerization under Hypersaline Conditions: A Robust Route to Phenolic Polymer‐Derived Carbon Aerogels (Angew. Chem. Int. Ed. 47/2016). Issue 47 (28th October 2016) - Yu, Zhi‐Long; Li, Guan‐Cheng; Fechler, Nina; Yang, Ning; Ma, Zhi‐Yuan; Wang, Xin; Antonietti, Markus; Yu, Shu‐Hong
Abstract : The polymerization of phenol–formaldehyde resin under hypersaline conditions, for example, in the presence of ZnCl2, generates a black monolith. In their Communication on page 14623 ff., N. Fechler, M. Antonietti, S. H. Yu et al. further show that a foam‐like carbon aerogel with good mechanical robustness can be directly obtained from the monolith without any special drying processes. ZnCl2 plays a key role in this process, serving as dehydration agent, foaming agent, and porogen.